Observation of the doubly strange b baryon Ωb- - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2008)
We report the observation of the doubly strange b baryon Ωb- in the decay channel Ωb-→J/ψΩ-, with J/ψ→μ+μ- and Ω-→ΛK-→(pπ-)K-, in pp̄ collisions at s=1.96TeV. Using approximately 1.3fb-1 of data collected with the D0 detector at the Fermilab Tevatron Collider, we observe 17.8±4.9(stat)±0.8(syst) Ωb- signal events at a mass of 6.165±0.010(stat)±0.013(syst) GeV. The significance of the observed signal is 5.4σ, corresponding to a probability of 6.7×10-8 of it arising from a background fluctuation. © 2008 The American Physical Society.